A comprehensive guide to energy production and development - Alvarado, Shannon (Energy science, engineering and technology series., 2020)
In A Comprehensive Guide to Energy Production and Development, a comprehensive analysis of existing examples in international practice regarding methods for massive implementation of renewable energy technology is provided. Following this, the authors assess alternative pathways for a future European energy system through the active involvement of relevant stakeholders according to their performance in key areas, such as the regulatory framework, market maturity, economic factors and stakeholder awareness towards a sustainable energy system, by using a multicriteria decision aid method. Recent developments in the field of electricity generation and distribution in Germany are presented, and decentralized forms of electricity generation and distribution are analyzed. As the consumption of power is increasing day by day, the power generation requirement is also increasing. As such, the authors discuss how renewable systems may be very useful in remote areas. The concluding paper studies the failure modes of wind turbine gearboxes and their causes. Factors affecting the gearbox reliability in both design and manufacturing processes are then analyzed.